Potential Impact of Subsequent Entry Biologics in Nephrology Practice in Canada - Daniel J Martinusen; Clifford Lo; Judith G Marin; Nicole W Tsao; Marianna Leung (Canadian Journal of Kidney Health and Disease, 2014)
Purpose of review: Subsequent entry biologics may soon be a reality in Canadian nephrology practice. Along with opportunities to reduce health care costs, these agents pose unique challenges that must be met for successful implementation. Understanding the experiences around the globe in both regulatory affairs and implementation will be a valuable guide for Canadian clinicians. This report provides an executive summary of the information required to guide decisions to use or implement subsequent entry biologics by comparing Canadian regulations to other developed nations, discussing their clinical issues and predicting their impact on the Canadian market and nephrology practice. We hope that this review will assist clinicians and policy makers to navigate this complex subject and to make informed decisions in the best interest of their patients. Sources of information: Sources of information include published literature and reports available in the public domain including guidelines obtained from regulatory agencies and information shared by Pharmaceutical companies. Lastly, we generated information from our own focus group consisting of nephrologists, a regulatory body representative, a hospital formulary representative, a patient representative, a hospital administrator, and a health economist. Findings: There exists a common and robust approach in the G20 countries for approval and regulation of subsequent entry biologics. Although by definition these agents do not have advantages (other than costs) or disadvantages compared to the original biologic, there are potential concerns and economic uncertainties regarding their implementation. Where SEBs are on the market, their market share is variable and modest. Limitations: We did not purchase third party reports for up to the minute marketing data. Since there are no subsequent entry biologics currently on the Canadian market, the information is only predictive. Implications: The nephrology community will have to work with patients, payers, and regulatory bodies to ensure safe and effective use of subsequent entry biologics. Cost savings can be achieved but these agents should only be used after fully understanding their unique challenges. At this time, they should not be automatically substitutable and only used for Health Canada-approved indications. Only through good pharmacovigilence will health care providers and patients become better informed.